Solid sharp-edged wire diamond dipole microstrip antenna: article / Sarah Yasmin Mohamad - Mohamad, Sarah Yasmin (2009)
This paper presents a solid sharp-edge wire diamond dipole microstrip antenna for UWB applications, operating within the range of 3.1-10.6GHz. A 3D electromagnetic simulator was used for designing and simulation of the antenna, with the following parameters; radiation efficiency of 88.14%, VSWR of 1.239, return loss of19.440dB and gain of 7.694dBi. The antenna was fabricated using RT Duroid 5870 substrate with a 2.33 relative permittivity and was fed by coaxial feed. An analysis of a prototype was carried out by using Vector Network Analyzer (VNA). It was observed that the simulated and the measured parameters agree with each other.